Are we teaching our students visual communication? Evaluation of writing assignments in public health. (2nd January 2020) - Anderson, Olivia S.; Kardia, Sharon; Gupta, Kashvi; August, Ella
Abstract: Visuals are an important means through which public health data can be communicated to diverse audiences, yet many public health students are not trained to develop effective visuals. We evaluated writing assignments from courses taught in public health schools and programmes accredited by the Council on Education for Public Health during the 2016–2017 academic year to identify whether they mentioned a visual element, whether the assignment explained how to create the visual, and if the visual element was worth points. Only 13 of 44 writing assignments mentioned a visual element and only two provided some instructions about how to create the visual element(s). Five assignments awarded points for visual elements. The lack of emphasis on visual elements in writing assignments is significant since visual communication is a key skill needed by practitioners to accompany writing to convey important public health information. Visual communication requires a critical thinking process and therefore time to develop the skills to create effective visuals is necessary. Thus, there is a crucial need for dedicated instruction for public health students to establish competence in visual communication.